The effect of corporate disclosure level on cost of equity capital / Nagaretham Thirumanickam and Ganisen Sinnasamy - Thirumanickam, Nagaretham; Sinnasamy, Ganisen (Institute of Research, Development and Commercialization (IRDC), 2006)
In today s changing business environment, the on going debate is between proponents and opponents of greater disclosure. The Asian financial crisis in 1997 further led to a wider recognition of the importance of quality corporate disclosure. However the benefits of greater disclosure are not well established and have proven difficult to quantify. This study attempts to examine the association between corporate disclosure score and cost of equity capital. While majority ofprior research in this discipline concentrated on the US and UK securities, this paper provides Malaysian evidence on this issue. Contrary to other research findings the results indicate that there is no significant relationship between the disclosure score and cost of equity which could be due to the loss of timeliness of information. As for the disclosure score, all companies showed an improvement over the years indicating the awareness for disclosure. NACRA companies showed good improvement on disclosure score as compared to the Industrial Products companies.